STUDY ON SEDIMENT TRANSPORT IN INNER AMBON BAY, MALUKU - JULISA (NIM : 22412001) , ELVIKA
Study on sediment transport in Inner Ambon Bay (TAD) in East-monsoon (June) and West-monsoon (November) 2014 is conducted using ECOMSED 3DBaroclinic model. River discharges and tides are use as the generating forces in the model. The inner bay’s current pattern are affected by tides, bathymetry, and shorelines. The highest speed of the horizontal current 0,2 – 0,3 m/s occurs in sill and decreases towards offshore approximately 0,1 m/s. The result shows that sediment was accumulated in the western, eastern, and northern of the inner bay. The highest concentration of the sediment in East-monsoon is approximately 40 – 75 mg/l and West- monsoon 18 – 25 mg/l which is occurs in 4 estuaries: Waiheru, Waitonahitu, Waisala, and Wailata. The concentration of sediment in Waireka is relatively small, i.e. 48-60 mg/l in East-monsoon and 18 – 23 mg/l in West- monsoon. The difference of suspended sediment concentration towards depth is 10 – 25 mg/l in East-monsoon and 5 – 10 mg/l in West- monsoon.